SOYGHURT SHELF LIFE OF PROBIOTICS AS A FILLER CHOCOLATE PRALINE - Raswen Efendi; Evy Rossi; Suherni Safitri Rangkuti (Jurnal Sagu, 2013)
The purpose of the research was to determine the storage limits of soyghurtprobiotics as a filler chocolatepraline. The research was done by using Completely Randomized Design (CRD) with five treatments (0,1,2,3and 4) weeks and 3 replications. The data obtained were analyzed by ANOVAand continued with Tukeytest at5% level. Results showed that the storage time significantly affected the moisture content, total lactic acidbacteria and total lactic acid. Levels of proteinandfatwereanalyzedbeforestoragesoyghurtis equal to 4.40%and 2.65%. Results of this study showed that storage time soyghurt probiotic chocolate praline as filler effecton water content, total BAL, and total lactic acid. Storage time 4 weeks resulted soyghurt containingmoisture content (85.45%), total BAL (10.34 log cfu/ml), and total lactic acid (0.51%) is still suitable forconsumption.Key words: soyghurt, shelf life, chocolate praline, whey, lactic acid bacteria